Leaves of Quercus ilex as Indicators of Airborne Trace Element Distribution in Lucca (Central Italy) - Francini, A.; Lorenzini, G.; Nali, C.; Loppi, S. (II INTERNATIONAL CONFERENCE ON LANDSCAPE AND URBAN HORTICULTURE, 2010)
Ambient air has always contained particles, ranging from sub-micrometric aerosols to clearly visible dust and sand grains. Plants have evolved to maximise light interception and CO2 assimilation and, as a consequence, they are also highly efficient receptors of airborne pollutants. The use of plant tissues has since long been shown to be an effective indicator of metal air pollution. Leaves of the evergreen species Quercus ilex were used as a passive sampler to describe the distribution of selected elements in the area around the walls of Lucca (Central Italy). Unwashed healthy mature leaves collected in June 2006 from 16 sampling sites were analysed by ICP-MS for Al, Ba, Be, Bi, Br, Ca, Cd, Cl, Co, Cr, Cs, Cu, Fe, K, Li, Mg, Mn, Mo, Na, Ni, Pb, Si, Ti, V and Zn. Values were normalised by subtracting baseline concentrations of biologically essential elements coming from Q. ilex plants collected into Botanical Garden of Lucca. Enrichment factors (EF) were calculated taking Al as crustal reference element. Cd, Cu and Zn exhibited the highest EF, with values ranging between 100 and 1000. Varimax rotated factor analysis allowed identifying three main source groups of elements, namely crustal components, sea-salt spray and anthropogenic sources (vehicular traffic, industrial activities). The factor one (crustal components) explained 48.3% of the total variance. Common high loadings for this factor were Al, Bi, Br, Co, Cu, Fe, Si, V, and Zn, which indicate a predominant soil contribution. Results are discussed with emphasis on the potential role of vegetation for the removal of particulate pollution.
The following values have no corresponding Zotero field: periodical: II INTERNATIONAL CONFERENCE ON LANDSCAPE AND URBAN HORTICULTURE pub-location: 999 RIVERVIEW DR, STE 208, TOTOWA, NJ 07512-1165 USA
Keywords: enrichment factor; factor analysis; ICP-MS; pollution

Measuring, modelling and testing ozone exposure, flux and effects on vegetation in southern European conditions--what does not work? A review from Italy. - Ferretti, M.; Fagnano, M.; Amoriello, T.; Badiani, M.; Ballarin-Denti, A.; Buffoni, A.; Bussotti, F.; Castagna, A.; Cieslik, S.; Costantini, A.; De Marco, A.; Gerosa, G.; et al. (Environmental pollution (Barking, Essex : 1987), 2007)
Ozone (O3) exposure at Italian background sites exceeds UN/ECE concentration-based critical levels (CLe(c)), if expressed in terms of AOT40. Yet the occurrence of adverse effects of O3 on forests and crops is controversial. Possible reasons include (i) ability of response indicators to provide an unbiased estimate of O3 effects, (ii) setting of current CLe(c) in terms of cut-off value and accumulation level, (iii) response functions adopted to infer a critical level, (iv) environmental limitation to O3 uptake and (v) inherent characteristics of Mediterranean vegetation. In particular, the two latter points suggest that critical levels based on accumulated stomatal flux (CLe(f)) can be a better predictor of O3 risk than CLe(c). While this concept is largely acknowledged, a number of factors may limit its applicability for routine monitoring. This paper reviews levels, uptake and vegetation response to O3 in Italy over recent years to discuss value, uncertainty and feasibility of different approaches to risk assessment.
The following values have no corresponding Zotero field: accession-num: 16889878
Keywords: AOTx; Critical levels; Effects; Mediterranean Region; Ozone; Stomatal flux